Descortinando bastidores: o olhar dos usuários internos dos museus paraibanos - Medeiros, Karlene Roberto Braga de (2013)
Named LETTING DOWN THE BACKSTAGE: THE LOOK OF THE PARAIBANOS MUSEUMS S INTERNAL USERS , this dissertation was thought from the Museum staff concerns, through monthly meetings of the Network of Educators in museums in Paraíba REM/PB, of which we are members. Such concerns led to reflections about the design they formulated of their workplace and if there was access and influence of formal and dominant concepts. This guided the elaboration of our goal which is to analyze the design of the museum from the perspective of the internal users of these memoryinstitutions in the state of Paraiba, specifically the active members of REM/PB. Accepting the definition of Costa et. al (2009) about user, and the one of Nuñez de Paula (2000) about internal user , we then call internal users the subjects hierarchically linked to the institution in which they work that, in need of information, use it. Thus, we consider as internal users of museums the subjects who use the information in their work in these institutions. On this documentary, exploratory and purposeful research, we used an auto-questionnaire as data collection method. It was applied after adjustments from the pre-test with the active members of REM/PB, regulars at least three annual meetings, over the internet (the most common form of communication between the members of REM/PB) and also in attendance. With quantitative and qualitative approach, the data were weighted based on content analysis (BARDIN; FRANCO). For this, categories were established and inserted in the chapters related to their respective theme. By this way, we believe that the internal user notice the REM/PB as a political, informative, cultural, symbolic and cultural space. This user considers himself a collaborator, an integral part of the museum and also its representative, perceiving himself as multifunctional and, despite pointing several problems found in museums, demonstrates satisfaction with his work. By this sense, the internal users conceive the museum as a dynamical space, the result of the (re) construction and (re) meanings of users ( internal and external ) to preserve the identity and culture of a people from informational and educational practices.